Sequentially deposited versus conventional nonfullerene organic solar cells: interfacial trap states, vertical stratification, and exciton dissociation - Zhang, Jiangbin; Futscher, Moritz H.; Lami, Vincent; Kosasih, Felix U.; Cho, Changsoon; Gu, Qinying; Sadhanala, Aditya; Pearson, Andrew J.; Kan, Bin; Divitini, Giorgio; Wan, Xiangjian; Credgington, Dan; et al. (Advanced energy materials, 2019)
Bulk heterojunction (BHJ) nonfullerene organic solar cells prepared from sequentially deposited donor and acceptor layers (sq-BHJ) have recently been shown to be highly efficient, environmentally friendly, and compatible with large area and roll-to-roll fabrication. However, the related photophysics at donor-acceptor interface and the vertical heterogeneity of donor-acceptor distribution, critical for exciton dissociation and device performance, have been largely unexplored. Herein, steady-state and time-resolved optical and electrical techniques are employed to characterize the interfacial trap states. Correlating with the luminescent efficiency of interfacial states and its nonradiative recombination, interfacial trap states are characterized to be about 40% more populated in the sq-BHJ devices than the as-cast BHJ (c-BHJ), which probably limits the device voltage output. Cross-sectional energy-dispersive X-ray spectroscopy and ultraviolet photoemission spectroscopy depth profiling directly visualize the donor-acceptor vertical stratification with a precision of 1-2 nm. From the proposed “needle” model, the high exciton dissociation efficiency is rationalized. This study highlights the promise of sequential deposition to fabricate efficient solar cells, and points toward improving the voltage output and overall device performance via eliminating interfacial trap states.
Gesehen am 15.05.2020